Nucleoside Drugs Induce Cellular Differentiation by Caspase-Dependent Degradation of Stem Cell Factors - Musch, Tanja; Öz, Yuva; Lyko, Frank; Breiling, Achim (PLOS ONE, 2010)
Background Stem cell characteristics are an important feature of human cancer cells and play a major role in the therapy resistance of tumours. Strategies to target cancer stem cells are thus of major importance for cancer therapy. Differentiation therapy by nucleoside drugs represents an attractive approach for the elimination of cancer stem cells. However, even if it is generally assumed that the activity of these drugs is mediated by their ability to modulate epigenetic pathways, their precise mode of action remains to be established. We therefore analysed the potential of three nucleoside analogues to induce differentiation of the embryonic cancer stem cell line NTERA 2 D1 and compared their effect to the natural ligand retinoic acid. Methodology/Principal Findings All nucleoside analogues analyzed, but not retinoic acid, triggered proteolytic degradation of the Polycomb group protein EZH2. Two of them, 3-Deazaneplanocin A (DZNep) and 2′-deoxy-5-azacytidine (decitabine), also induced a decrease in global DNA methylation. Nevertheless, only decitabine and 1β-arabinofuranosylcytosine (cytarabine) effectively triggered neuronal differentiation of NT2 cells. We show that drug-induced differentiation, in contrast to retinoic acid induction, is caused by caspase activation, which mediates depletion of the stem cell factors NANOG and OCT4. Consistent with this observation, protein degradation and differentiation could be counteracted by co-treatment with caspase inhibitors or by depletion of CASPASE-3 and CASPASE-7 through dsRNA interference. In agreement with this, OCT4 was found to be a direct in-vitro-target of CASPASE-7. Conclusions/Significance We show that drug-induced differentiation is not a consequence of pharmacologic epigenetic modulation, but is induced by the degradation of stem-cell-specific proteins by caspases. Our results thus uncover a novel pathway that induces differentiation of embryonic cancer stem cells and is triggered by the established anticancer drugs cytarabine and decitabine. These findings suggest new approaches for directly targeting the stem cell fraction of human tumours.